Gas phase diagnostics during silicon carbide films deposition using very high frequency - plasma enhanced chemical vapor deposition - Mustapha, N. (2015)
In-situ Optical Emission Spectroscopy was used as diagnostics tool to monitor deposition process of Silicon Carbide (SiC) film using Very High Frequency - Plasma Enhanced Chemical Vapor Deposition (VHF-PECVD) method. The VHF-PECVD operated at plasma excitation frequency of 150MHz and 25 W of RF power was applied to generate plasma. A mixture of silane, SiH 4 and methane, CH 4 was used as a precursor to deposit SiC. Ar was used as a carrier gas and H 2 was added to enhance the formation of SiC. The intensities of SiH∗ (414 nm), CH∗ (431 nm), H α (656 nm) and H β (486 nm) lines were monitored during the deposition process at different deposition parameters. The results indicate that the substrate temperature, methane flow rate, and hydrogen flow rate affect the emission intensities for all species inside the plasma.